Ewa – pierwsza kobieta w świetle pism świętego Augustyna - Żurek, Antoni (Vox Patrum, 2016)
The biblical story of creation, and subsequently the sin of Eve, was frequently analized by many Church Fathers. These analysis conclusions were ones of the crucial elements which shaped the vision of woman in the Early Christian times. St. Augustine was within this trend. He analized and referred to the Genesis’ texts related to Eve in the numerous of his works. He read this story either literally or alegorically. From the biblical texts which were interpreted literally, he derived his view about human sexuality and its purposefulness. He also eagerly emphasized the issue of woman’s nature. Indeed, he acknowledged that Eve was equal to Adam as human, as well as woman was equal to male at all. Nevertheless, he was sure of woman’s nature weakness and affirmed her dependence on male in the social life. St. Augustine used the alegorical interpretation conclusions to explain the relationship between the body and spirit within a man. In this perspective, the woman’s position is especially weak because, as a representant of body, she should be totally dependent on male who symbolizes the spiritual sphere within a man. The article only fragmentalically presents the St. Augusine’s view on the woman question because it is limited only to the conclusions of one biblical text exegesis.